Burn healing plants in Iranian Traditional Medicine - Sh. Fahimi; H. Hajimehdipoor; M. Abdollahi; S.A. Mortazavi (Iranian Society of Pharmacognosy, 2015)
Burns are known as one of the most common forms of injury with devastating consequences. Despite the discovery of several antiseptics, burn wound healing has still remained a challenge to modern medicine. Herbal products seem to possess moderate efficacy with no or less toxicity and are less expensive compared to synthetic drugs. Burn is a well-known disorder in Iranian Traditional Medicine (ITM). Iranian physicians have divided burns into various types based on the cause and recommended treatment for each type. According to ITM references, herbal therapy was the major treatment prescribed by Iranian physicians for burns. In the present study, seven ancient Iranian medical texts were screened for the herbs with burn healing effects along with their applied dosage forms. The medicinal herbs were listed and scored based on the frequency of their repetition. Moreover, the best scientific name that was suitable for each plant as well as surveying modern studies about their biological effects has been carried out. In our investigation eighteen plants with seven topical application categories have been obtained as the most frequent herbs for burn healing in ITM. Modern studies have revealed that these plants have shown some biological activities such as anti-inflammatory, antimicrobial and antioxidant effects which might establish the relationship between the mentioned activities and burn wound healing property. This list can provide a suitable resource for future researches in the field of burn treatment.